Mikrotia - Ruby Ruana A. (Universitas Muhammadiyah Malang, 2011)
Microtia is an incompletely formed ear. The term “micro” means small and “otia” means ear. Hence, when translated literally,“microtia” means small ear. At times a bump of tissue is present in the location where an ear would normally be found. In other cases,the lobule, the lower part of the ear, and the concha, the hollow part of the ear, may be partially formed and the entire upper part ofthe ear is missing. Although microtia can involve one ear or both ears, 80% of the time only one is affected. An estimate of the occurance of microtia is one in 6000 births. In this literature review will discuss the reconstruction of mikrotia